The Determinants of Micro-Enterprise Resilience: A Bibliometric Analysis and Empirical Evidence on The Mediating Role of Innovation Capability in the Relationship Between Human Capital and Islamic Financing - Eti Jumiati; Endah Robiatul Adawiyah; Mahmud Syukri; Diwa Lulu Qurotulaini; Budiman (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose: This study aims to analyze the determinants of micro-enterprise resilience by emphasizing the role of human capital, Islamic financing, and innovation capability as mediating variables. Design/Method: The study employed a mixed-methods approach, combining bibliometric analysis and quantitative approaches. Bibliometric analysis was conducted to map the development, trends, and intellectual structure of research using Scopus data, while a quantitative approach was used to test causal relationships between variables using the SEM-PLS method with data from micro-enterprises in Purwakarta Regency. Findings: The results showed that human capital had a positive and significant effect on innovation capability and micro-enterprise resilience, and innovation capability had a significant effect on resilience. Islamic financing has a significant effect on innovation capability, but not a direct effect on resilience. Furthermore, innovation capability was shown to mediate the relationship between human capital and Islamic financing on micro-enterprise resilience. Implications: The implications of this study emphasize the importance of strengthening human resource quality and enhancing innovation capabilities as key strategies in enhancing micro-enterprise resilience, as well as the need to optimize Islamic financing to encourage innovation and business sustainability.